Pelatihan Pembuatan Aset Digital Berupa Foto Sebagai Alat Promosi untuk Pengurus Kelompok Tani Mustika - Rofi'i, Muhammad; Nugroho, Randhy; Gani, Ariel Nian; Faisal, Muhammad; Luhur, Alfariz; Zhafira, Nayla Endhita (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2025)
Training activities for creating promotional content through product photography for Poktan Mustika administrators were held in two locations, namely at Jl. Kerja Bakti No. 23, Kramat Jati, East Jakarta, and in the Smartclassroom Room of YARSI University. The training participants were the daily administrators of Poktan and were tasked with creating photo content for product promotion. This training aimed to improve participants' understanding of basic product photography techniques, including exposure settings, lighting, composition, use of aids, and simple photo editing. Training evaluation was carried out through pre-tests and post-tests with 13 indicators of understanding. The results showed an increase in the average understanding of participants from 2.51 to 4.49 (scale 1-5), or an increase of 78.57%. The highest increase was seen in the aspects of lighting settings, photo composition, and the use of manual camera mode, while the lowest increase was in the ability to explore shooting angles. In addition, all participants stated that their insight had increased and they were satisfied with this activity with an average satisfaction level of 4.67 (scale 1-5). Overall, this training activity was deemed successful and effective in improving participants' product photography skills for digital promotional purposes.